STBUR: Sleep trouble breathing and unrefreshed questionnaire: Evaluation of screening tool for postanesthesia care and disposition. Issue 8 (10th July 2019) - Galvez, Jorge A.; Yaport, Miguel; Maeder‐Chieffo, Susan; Simpao, Allan F.; Tan, Jonathan M.; Wasey, Jack O.; Lingappan, Arul M.; Jablonka, Denis H.; Subramanyam, Rajeev; Ahumada, Luis M.; Song, Bo; Wu, Lezhou; et al.
Abstract: Background: The Snoring, Trouble Breathing, and Un‐Refreshed (STBUR) questionnaire is a five‐question screening tool for pediatric sleep‐disordered breathing and risk for perioperative respiratory adverse events in children. The utility of this questionnaire as a preoperative risk‐stratification tool has not been investigated. In view of limited availability of screening tools for preoperative pediatric sleep‐disordered breathing, we evaluated the questionnaire's performance for postanesthesia adverse events that can impact postanesthesia care and disposition. Methods: The retrospective study protocol was approved by the institutional research board. The data were analyzed using two different definitions for a positive screening based on a five‐point scale: low threshold (scores 1 to 5) and high threshold (score of 5). The primary outcome was based on the following criteria: (a) supplemental oxygen therapy following postanesthesia care unit (PACU) stay until hospital discharge, (b) greater than two hours during phase 1 recovery, (c) anesthesia emergency activation in the PACU, and (d) unplanned hospital admission. Results: About 6025 patients completed the questionnaire during the preoperative evaluation. And 1522 patients had a low threshold score and 270 had a high‐threshold score. We found statistically significant associations in three outcomes based on the low threshold score: supplemental oxygen therapy (negative‐predictive value [NPV] 0.97, 95% CI 0.97‐98), PACU recovery time (NPV 0.99, 95% CI 0.99‐0.99) and escalation of care (NPV 0.98, 95% CI 0.97‐0.98). Positive‐predictive values were statistically significant for all outcomes except anesthesia emergency in the PACU. Conclusion: The Snoring, Trouble Breathing, and Un‐Refreshed questionnaire identified patients at higher risk for prolonged phase 1 recovery, oxygen therapy requirement, and escalation of care. The questionnaire's high‐negative predictive value and specificity may make it useful as a screening tool to identify patients at low risk for prolonged stay in PACU.